CARDIOVASCULAR PATHOLOGY IN ACUTE STROKE (ISSUES ON PREVALENCE, PREVENTION AND TREATMENT) - S. A. Rumjantseva; R. G. Oganov; E. V. Silina; V. A. Stupin; S. B. Bolevitch; A. S. Orlova; E. N. Kabaeva; S. A. Volik; O. N. Sokhova; A. Yu. Kubotchkin (Кардиоваскулярная терапия и профилактика, 2014)
The article concerns on the problems of vascular comorbidity epidemiology and pathophysiological aspects of heart disease, which became a leading etiopathologic factor of cerebral infarctions and hemorrhages. The relationship between coronary artery disease (CAD), atrial fibrillation, hypertension and cerebral infarction types is emphasized.Aim. To analyze the role of comorbidity, attributable to cardio-vascular pathology in the initiation, course, clinical features and outcomes of cerebral infarction.Material and methods. We performed a prospective study, including 1072 patients with stroke, attributable to various cardiovascular pathology, evaluated the influence of vascular comorbidity of variable degree on the course and outcomes at an inpatient stage and at follow-up.Results. We demonstrated a negative influence of CAD, atrial fibrillation and postinfarction cardiosclerosis on the incidence of cerebral infarction, unfavorable course of the disease and functional outcomes at inpatient stage. The combination of vascular comorbidity resulted in an increased mortality in post-stroke period during 6 years of follow-up.Conclusion. Epidemiology of vascular comorbidity, its role in cerebrovascular accidents in patients with cardiac pathology justifies the need of active realization of contemporary multidisciplinary prevention programs, prolonged instrumental monitoring and implementation of energy deficiency correction therapy in comprehensive treatment programs.